2001
DOI: 10.1063/1.1359780
|View full text |Cite
|
Sign up to set email alerts
|

The role of high-temperature island coalescence in the development of stresses in GaN films

Abstract: The formation of dislocations and stress in GaN layers grown by metalorganic vapor phase epitaxy on sapphire is investigated with regard to the average grain diameter. The grain diameter was determined by monitoring the high-temperature GaN island coalescence process during growth using reflectometry. It is found that the density of edge threading dislocations decreases and the compressive stress measured after cooling to room temperature increases when the coalescence thickness and the grain diameter increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(124 citation statements)
references
References 17 publications
12
110
1
1
Order By: Relevance
“…The residual strain on the Al 0.62 Ga 0.38 N buffer layers was caused by strains associated with the growth process, i.e., the lattice mismatch of 13.4% between the buffer and the sapphire, and the compressive thermal mismatch strain that developed while cooling to room temperature. 9 The lattice mismatch between the Al 0.62 Ga 0.38 N buffer layer and sapphire was relaxed by 98%. This extent of relaxation corresponds to a residual strain of approximately −0.27% ͑i.e., compressive͒ in the Al 0.62 Ga 0.38 N. The strain in the Al 0.62 Ga 0.38 N layer due to thermal-expansion mismatch with the sapphire is estimated to be ϳ−0.30%.…”
Section: Resultsmentioning
confidence: 99%
“…The residual strain on the Al 0.62 Ga 0.38 N buffer layers was caused by strains associated with the growth process, i.e., the lattice mismatch of 13.4% between the buffer and the sapphire, and the compressive thermal mismatch strain that developed while cooling to room temperature. 9 The lattice mismatch between the Al 0.62 Ga 0.38 N buffer layer and sapphire was relaxed by 98%. This extent of relaxation corresponds to a residual strain of approximately −0.27% ͑i.e., compressive͒ in the Al 0.62 Ga 0.38 N. The strain in the Al 0.62 Ga 0.38 N layer due to thermal-expansion mismatch with the sapphire is estimated to be ϳ−0.30%.…”
Section: Resultsmentioning
confidence: 99%
“…3). Actually, HVPE-grown material as investigated here is well known to be under significant tensile strain [24,25], and we therefore tentatively assign the stabilization of the four-core struc- ture as a consequence of significant tensile strain in the sample. Furthermore, the effect of Ga and N vacancies on the stability of the dislocation core has been considered.…”
mentioning
confidence: 93%
“…Differently, in epitaxial GaN, compressive stress generally dominates, because of the larger thermal expansion coefficient of sapphire. 51,[56][57][58][59][60] Large compressive stresses were also reported in films deposited by RF sputtering for substrate temperatures below 500 C. 25 Both the previous literature 39-41,51,52,56,61 and our analysis of the data in the present study indicate that the observed lattice swelling (with changes in both a and c parameters of the GaN hexagonal cell) can be attributed to three main factors: (i) the coalescence/merging of the crystallites/interfaces; 56 (ii) the loss of film material during and after growth; and (iii) impingement of energetic N and the corresponding creation of selfinterstitials. 34,41,52,62,63 These points are discussed in more detail in the following.…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects largely overcame the compressive stress resulting from the smaller expansion coefficient of GaN in relation to the sapphire substrate, which has been generally observed on epitaxially grown samples. 56,59,60 In the low temperature range (T s < 500 C), the thicker layers are expected to decrease the "memory" effect of the film-substrate interface, helped by the wider grain boundaries and amorphous regions present.…”
Section: Discussionmentioning
confidence: 99%